Tactile 3D-printed media interaction with the color surface features of paintings. The case of the Scream (1910?) painting - Stavroulakis, Petros Ioannis; Pagano, Alfonsina; Boracchi, Beatrice; Siozos, Panagiotis; Sotiropoulou, Sophia; Leonhardt, Emilien; Sabatier, Vincent; Trumpy, Giorgio; Sandu, Irina C. A. (Frontiers in Computer Science, 2025)
Due to their fragility and uniqueness, valuable works of art are largely unavailable for direct interaction with the public. They are usually displayed in conditions that restrict access, which inevitably limits the visitor experience, particularly for audiences with reduced mobility and visual impairments. Furthermore, related information is not easily conveyed because of the limited time visitors have to browse the museum, and because it is usually presented in jargon that assumes scientific knowledge, or is presented out of context. In this paper, we aim to address all these aspects simultaneously, using the painting The Scream (1910?) from the MUNCH Museum in Oslo as a case study. A combination of high-resolution imaging and computer vision algorithms was used to identify and separate the color surface features for two areas of the painting. The information was then presented to visitors by 3D printing the two areas and placing the color surface features at different heights, creating a relief structure that could be touched and inspected up close. The novel and highly accessible experience was evaluated at the InArt24 conference and at the KHM Museum in Oslo, Norway. During the evaluations, participants reported that interacting with the physical 3D replicas stimulated their interest and motivation, and increased their satisfaction when learning about the painting's color characteristics. These initial findings suggest that presenting information about art objects through multisensory experiences can greatly enhance accessibility and engagement for diverse audiences.